An Authentic Assessment of Students with Special Educational Needs - เล่าสัม ธัญสินี (Journal Of Ratchasuda Institute for Research and Development of Persons With Disabilities, 2020)
An authentic assessment is an alternative and effective tool that can be used with An authentic assessment is an alternative and effective tool that can be used with special educational need students. The tool focuses on the assessment of actual performance of individuals’ learning objectives. It covers the 3 student learning skills - cognitive, affective, and psychomotor. The test is mostly used for the assessment of cognitive skill whereas the observation and interview are widely used for the assessment of affective domain. The performance assessment and student folios are used in assessing psychomotor development. However, the selection of the tools suitable for the different needs of individual students is dependent on the judgment of the assessor. The special educational needs of individuals should be given a high concern; these include special assistance during the test required by individuals, the preparation of the test, testing rooms, testing facilities and environment, and testing schedule. This will help the test administrator effectively and efficiently manage the test, and consequently come up with an authentic result.